Calorie restriction prevents diet‐induced insulin resistance independently of PGC‐1‐driven mitochondrial biogenesis in white adipose tissue. Issue 2 (2nd October 2018) - Pardo, Rosario; Vilà, Maria; Cervela, Luis; de Marco, Marina; Gama-Pérez, Pau; González-Franquesa, Alba; Statuto, Lucia; Vilallonga, Ramon; Simó, Rafael; Garcia-Roves, Pablo M.; Villena, Josep A.
ABSTRACT: Calorie restriction (CR) exerts remarkable, beneficial effects on glucose homeostasis by mechanisms that are not fully understood. Given the relevance of white adipose tissue (WAT) in glucose homeostasis, we aimed at identifying the main cellular processes regulated in WAT in response to CR in a pathologic context of obesity. For this, a gene‐expression profiling study was first conducted in mice fed ad libitum or subjected to 40% CR. We found that the gene network related to mitochondria was the most highly upregulated in WAT by CR. To study the role that increased mitochondrial biogenesis plays on glucose homeostasis following CR, we generated a mouse model devoid of the coactivators peroxisome proliferator‐activated receptor ³ coactivator 1 (PGC‐1)α and PGC‐1β specifically in adipocytes. Our results show that mice lacking PGC‐1s in adipocytes are unable to increase mitochondrial biogenesis in WAT upon CR. Despite a blunted induction of mitochondrial biogenesis in response to calorie deprivation, mice lacking adipose PGC‐1s still respond to CR by improving their glucose homeostasis. Our study demonstrates that PGC‐1 coactivators are major regulators of CR‐induced mitochondrial biogenesis in WAT and that increased mitochondrial biogenesis and oxidative function in adipose tissue are not required for the improvement of glucose homeostasis mediated by CR.—Pardo, R., Vila, M., Cervela, L., de Marco, M., Gama‐Pérez, P., González‐Franquesa, A., Statuto, L., Vilallonga, R., Simó, R., Garcia‐Roves, P. M., Villena, J. A. Calorie restriction prevents diet‐induced insulin resistance independently of PGC‐1‐driven mitochondrial biogenesis in white adipose tissue. FASEB J. 33, 2343–2358 (2019). www.fasebj.org